Modulation of the optoelectronic properties of polyimide (Kapton-H) films by gamma irradiation for laser attenuation and flexible space structures. (May 2022) - Ismail, A.M.; Nasrallah, D.A.; El-Metwally, E.G.
Abstract: polyimide (PI or Kapton-H) has proven its potential in the field of optoelectronic, nuclear technology and space industry due to its excellent electric insulation, transparency and flexibility. The present study focuses the effect of γ-irradiation (0, 25, 50 and 100 Mrd) on the structural, optical, AC electrical conductivity and dielectric properties of PI film samples. In the results, the crystallite size was shown to be increased from 37.77 to 73.42 Å in the X-ray diffraction XRD study. Certain variations in assignment bands like (O–H) stretching and carbonyl (CO) symmetric stretching were observed in FTIR spectrum. A shift in the absorption edge is observed in the UV–vis spectroscopy to higher wavelengths and consequently a decrease in both direct and indirect band gap energy E g o p t . The calculated values of the refractive index n is also increased upon γ-irradiation. The parameters of Wemple - DiDomenico (WDD) are calculated for pristine and γ-irradiated film samples. The dependence of the dissipation factor t a n δ and optical conductivity σ o p t are studied as a function of the photon energy ( h ν ) at different γ-doses. Moreover, the 3rd order non-linear susceptibility χ ( 3 ) and non-linear index of refraction n 2 were also studied. Optical limiting measurements indicate that irradiation of PI samples with high γ-dose (100 Mrd) highly attenuated the laser beams (532 and 632.8 nm) which may be useful for use in optoelectronic laser limiters and filters. The AC electrical conductivity σ a c, dielectric constant ε ′ and dielectric loss ε ″ are also investigated in the range of frequency (100 Hz - 1 MHz). The values of σ A C are enhanced by irradiation with γ-rays and the behaviors of the frequency exponent s indicates that the AC conduction in PI samples is governed by the correlated barrier hopping (CBH) mechanism. Highlights: Polyimide (Kapton-H) films were irradiated with γ-rays of doses 25 Mrd to 100 Mrd. γ-irradiation affects the structural properties of polyimide samples. Optical parameters of the polyimide films are correlated with absorbed dose. Irradiation of polyimide with 100 Mrd γ-rays highly attenuated laser beams. AC electrical conductivity σ A C of polyimide enhanced with γ-irradiation.